Stage acoustics and parametric design: The development of an integrated early design tool. Issue 3 (September 2021) - Sanz Soriano, Javier; Wright, Oliver; van den Braak, Elisabeth; Day, Christopher
Traditional ray tracing software tools (e.g. Odeon, CATT-Acoustic, EASE) enable detailed analysis of stage acoustics; however, they are typically undertaken in later design stages and lack the flexibility required for early design development. This paper, which follows from a poster presentation at ISRA 2019, investigates the use of a three-dimensional modelling platform (Rhinoceros/Grasshopper) to quickly assess the influence of architectural changes on reflections that support orchestral ensemble. This approach enables immediate feedback, a more creative design process and better integration of architecture and acoustics. Early reflections have been found to be vital for effective orchestral ensemble. Therefore, the study focused on the investigation of early energy distribution on stage with ray tracing analysis using a parametric tool. This tool also considers cross-stage shielding effects from the orchestra and the directivity of instruments. The results of the tool have been compared to an existing acoustic modelling software to determine its accuracy and reliability. Additionally, the expansion of the tool with an evolutionary solver has also been explored. The development of a Rhinoceros/Grasshopper design tool has been found to be beneficial in the analysis of stage conditions and enhances the design collaboration during early design phases.